Effects of Oral Exposure to Mn-Doped ZnS Quantum Dots on Intestinal Tract and Gut Microbiota in Mice - Yang, Yanjie; Xia, Ruixue; Zhang, Xiaomei; Wang, Xu; Zhou, Yuchen; Wang, Honggang; Feng, Yu; Lv, Shuangyu; Ji, Shaoping (Frontiers in Physiology, 2021)
Mn doped ZnS quantum dots (QDs) with excellent optical properties, have been explored in a wide range of fields. Their potential adverse effects on biological systems and human health should be evaluated before bioapplication. In the present study, we investigate the effect of Mn doped ZnS QDs on intestinal tract and gut microbiota structures at 2 hours (h) and 14 days (d) after 14 d repeated oral exposure in mice. Flame atomic absorption spectrophotometry (FAAS), histopathological examinations and transmission electron microscopy (TEM) was applied to assess the absorption and toxicity of Mn doped ZnS QDs on intestinal tract. 16s rRNA gene sequencing were employed to evaluate the gut microbial communities. Our results demonstrated that Mn doped ZnS QDs did not accumulate in duodenum, jejunum, ileum, and colon. The Zn contents of feces samples were not significantly higher than control group. No major histological changes were found in these tissues. The microvilli of intestinal tract kept regular, but swelling of mitochondria and endoplasmic reticulum were detected by TEM at 14 d after the last gavage. A total of 2712 operational taxonomic units (OTUs) were generated. Mn-doped ZnS QDs treatment could not significantly change the α-diversity indexes of Richness, Chao1, Shannon and Simpson indexes. According to the result of principal component analysis (PCA), Mn-doped ZnS QDs had no effect on the overall structure of the gut microbiota. No significant change was occurred at the phylum level, while three genus were downregulated at 2 h and seven genus changed at 14 d after the last gavage. Our findings revealed that Mn-doped ZnS QDs had a little stimuli on intestinal tract and gut microbiota, and oral administration may be a safety route for bioapplication.